Morphological variation of selected species in the genus orthetrum (odonata : anisoptera) in sarawak - Nurulain, Binti Samsudin. (Universiti Malaysia Sarawak (UNIMAS), 2013)
Dragonflies are widely distributed in the tropical rainforests of the island of Borneo. Dragonflies can be differentiated morphologically at the species level. Study on the morphological variations of four selected species in the genus Orthetrum (i.e. Orthetrum glaucum, Orthetrum testaceum, Orthetrum chrysis, and OrthetnJm sabina) from the suborder Anisoptera in Sarawak was conducted by using voucher specimens deposited in UNIMAS Zoological Museum, Sarawak Forestry Research Centre, and Sarawak Biodiversity Centre. This study was done to determine the morphological variations among dragonflies species based on morphometric characters and to identify the important characters that differentiate the individuals at the species level. A total number of 89 adult individuals were morphologically analysed with 15 morphometric measurements. Cluster Analysis (CA) and Discriminant Function Analysis (DF A) showed that Orthetrum sabina can be discriminated from Orthetrum glaucum, Orthetrum testaceum, and Orthetrum chrysis mainly based on four major diagnostic characters; length of abdomen, length of thorax, width of thorax, and length of tarsus (hind leg). However, none of the canonical coefficients estimated from the measured characters are suitable to distinguish Orthetrum glaucum, Orthetrum testaceum, and Orthetrum chrysis from each other. The knowledge from this morphometric analysis will assist researchers to choose the best characters to discriminate between the Orthetrum species for future research.